A Pilot Study to Assess Opportunistic Use of CT-Scan for Osteoporosis Screening in Chronic Pancreatitis - McNabb-Baltar, Julia; Manickavasagan, Hanisha R.; Conwell, Darwin L.; Lu, Andrew; Yadav, Dhiraj; Hart, Philip A.; Lara, Luis F.; Cruz-Monserrate, Zobeida; Ing, Steven; Hinton, Alice; Mace, Thomas A.; Bradley, David; et al. (Frontiers in Physiology, 2022)
Objectives: CT scans are commonly performed in patients with chronic pancreatitis (CP). Osteopathy and fractures are recognized in CP but no osteoporosis screening guidelines are recommended. Assess “opportunistic” CT scan derived bone density thresholds for identifying osteoporosis in CP. Methods: Retrospective pilot cohort study. CP subjects who had CT scan and Dual energy x-ray absorptiometry (DXA) within 1 year were included. CT-derived bone density was measured at L1 level. Pearson correlation was performed between age and CT-derived bone density in Hounsfield unit (HU). Univariate analysis using HU to identify osteoporosis was performed at various thresholds of bone density. The discriminatory ability of the model was evaluated with the area under the receiver operating characteristic (ROC) curve (AUC). Several HU thresholds were tested. Results: 27 CP subjects were included, of whom 11 had normal bone density, 12 osteopenia and 4 osteoporosis on DXA. Mean age was 59.9 years (SD 13.0). There was a negative correlation of age with HU (r=-0.519, p=0.006). CT-derived bone density predicted DXA-based osteoporosis in the univariable analysis (Odds Ratio [OR]=0.97 95% Confidence Interval [CI] 0.94-1.00, p=0.03). HU thresholds were tested. A threshold of 106 HU maximized the accuracy (AUC of 0.870). Conclusions: CT-scan may be repurposed for “opportunistic” screening to rule-out osteoporosis in CP. A larger study is warranted to confirm these results.